Cucurbitacin B Induces Hypermethylation of Oncogenes in Breast Cancer Cells - Dittharot, Kanthanadon; Dakeng, Sumana; Suebsakwong, Parichat; Suksamrarn, Apichart; Patmasiriwat, Pimpicha; Promkan, Moltira (Planta Medica, 2019)
Breast cancer is a complex disease driven by multiple factors including both genetic and epigenetic alterations. Recent studies revealed that abnormal gene expression induced by epigenetic changes including aberrant promoter methylation plays a critical role in human breast carcinogenesis. Cucurbitacin B has antiproliferative activity against various human breast cancer cells, but the molecular mechanism is not completely understood. In this study, we explore the influence of cucurbitacin B from Trichosanthes cucumerina on the methylation status at the promoter of oncogenes c-Myc, cyclin D1, and survivin in breast cancer cell lines. Growth inhibitory effect of cucurbitacin B on breast cancer cells was assessed by MTT assay and colony formation assay. Methylation status of genomic DNA was determined by methylation-specific PCR. Gene and protein expression levels of all genes studied were analyzed by real-time RT-PCR and western blot. The results indicated that cucurbitacin B could inhibit cell growth in breast cancer cells. The oncogene promoters are usually hypomethylated in cancer cells. Upon cucurbitacin B treatment, upregulation of DNMT1 and obvious heavy methylation in the promoters of c-Myc, cyclin D1, and survivin, which consequently downregulated the expression of all these oncogenes, were observed. Hence, cucurbitacin B proved to be a potential cancer therapeutic agent, in part by inducing hypermethylation and silences the oncogenic activation.
Keywords: cucurbitacin B; Trichosanthes cucumerina; Curcubitaceae; hypermethylation; breast cancer; anticancer